A simulation-based optimization evaluating process and feed system effect in plastic injection molding - Onyiego, Joshua M.; Wakiru, James M.; Keraita, James N. (International journal on interactive design and manufacturing, 2025)
Although technological advancements have brought about the inventions of hot runner injection molding machines, cold runner injection molding machines are still in application and are subject to many defects associated with filling such as short shots and sink marks. Many studies have, therefore, been carried out in an attempt to optimize and minimize defects. These studies have, however, not studied several combinations of input parameters and their effects on sink marks and short shots. The highlighted inadequacies of previous studies have led this research to investigate the effect of variation of feed system features and process parameters on short shot and sink mark defects. Through Computer Aided Engineering (CAE), Design of Experiments (DoE), and data analysis the study determined the effects of variation of process parameters, runner and gate shapes on the selected performance measures. A Taguchi L27 orthogonal array was undertaken for optimization based on three levels of runner shape, gate shape, melt temperature, injection pressure limit and filling time and the responses in short shot possibility and sink marks determined at each input combination based on DIX-SI grade polystyrene material. Parameters found to have the most critical effect on short shot defects included melt temperature, injection pressure, and runner shape, whereas those with the most critical effect on sink marks were fill time, gate shape and runner shape.